Who Would Pay for State Alcohol Tax Increases in the United States? - Naimi, Timothy S. (Prev Chronic Dis, 2016)
INTRODUCTION: Despite strong evidence that increasing alcohol taxes reduces alcohol-related harm, state alcohol taxes have declined in real terms during the past 3 decades. Opponents of tax increases argue that they are unfair to “responsible” drinkers and those who are financially disadvantaged. The objectives of this study were to assess the impact of hypothetical state alcohol tax increases on the cost of alcohol for adults in the United States on the basis of alcohol consumption and sociodemographic characteristics. METHODS: The increased net cost of alcohol (ie, product plus tax) from a series of hypothetical state alcohol tax increases was modeled for all 50 states using data from the 2011 Behavioral Risk Factor Surveillance System, IMPACT Databank, and the Alcohol Policy Information System. Costs were assessed by drinking pattern (excessive vs nonexcessive) and by sociodemographic characteristics. RESULTS: Among states, excessive drinkers would pay 4.8 to 6.8 times as much as nonexcessive drinkers on a per capita basis and would pay at least 72% of aggregate costs. For nonexcessive drinkers, the annual cost from even the largest hypothetical tax increase ($0.25 per drink) would average less than $10.00. Drinkers with higher household incomes and non-Hispanic white drinkers would pay higher per capita costs than people with lower incomes and racial/ethnic minorities. CONCLUSION: State-specific tax increases would cost more for excessive drinkers, those with higher incomes, and non-Hispanic whites. Costs to nonexcessive drinkers would be modest. Findings are relevant to developing evidence-based public health practice for a leading preventable cause of death.